2010
DOI: 10.12660/joscmv3n2p61-77
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Information and Knowledge Sharing on Supply Chain Performance: A Survey Based Approach

Abstract: Supply chain management emphasizes the overall and long-term benefit of all parties on the chain through cooperation and information sharing. Recently, information sharing is attaining the concentration of the researchers. Majority of the previous work is on the individual effect of information and knowledge sharing on performance. This paper aims to focus on the combined consequence of infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 36 publications
4
60
0
Order By: Relevance
“…For instance, the partnership of Procter and Gamble (P&G) and Wal-Mart, P&G as an information and capital rich manufacturer, while Wal-Mart as an information and capital rich retailers get a win-win cooperation of information sharing across their mutual supply chain and achieve mutual benefits and enhanced both supply chain performance. In short, Rashed et al (2010) concluded that a good partnership with suppliers positively impacts on the operational performance of the organization. Inversely, the low dependency on supplier partnership is led to the worst in the supply chain performance.…”
Section: Supply Chain Capabilities and Supply Chain Operational Perfomentioning
confidence: 99%
“…For instance, the partnership of Procter and Gamble (P&G) and Wal-Mart, P&G as an information and capital rich manufacturer, while Wal-Mart as an information and capital rich retailers get a win-win cooperation of information sharing across their mutual supply chain and achieve mutual benefits and enhanced both supply chain performance. In short, Rashed et al (2010) concluded that a good partnership with suppliers positively impacts on the operational performance of the organization. Inversely, the low dependency on supplier partnership is led to the worst in the supply chain performance.…”
Section: Supply Chain Capabilities and Supply Chain Operational Perfomentioning
confidence: 99%
“…The study presented in (Ajay & Maharaj, 2010) reveals that IS has a great impact on the overall cost of running a successful supply chain, and improves the holistic management of supply chain activities. Rashed, Azeem, & Halim (2010) have explored the combined effect of information and knowledge sharing on supplier's operational performance. In particular, they have showed that information sharing is a prerequisite for knowledge sharing and the close supplier-buyer relationship is a vital factor for escalating the supplier's operational performance.…”
Section: Information Sharing and Supply Chain Performancementioning
confidence: 99%
“…To add some distinction, a supply chain in which knowledge is shared is actually a progression of the information-based supply chain. This is because knowledge is considered a more valuable, more practically advantageous type of information, in the lexicon of organizations (Rashed, Azeem & Halim, 2010). That being said, it is the precision, timeliness, suitability, and trustworthiness of information exchanged throughout the supply chain that determines the quality of that information (Li, Ragu-Nathan, Ragu-Nathan, Rao & Subba, 2006).…”
Section: Information and Knowledge Sharingmentioning
confidence: 99%